The division of labour, worker organisation, and technological change - Lex Borghans; Bas ter Weel (Institute for the Study of Labor (IZA), 2005)
The model developed in this paper explains differences in the division of labour across firms as a result of computer technology adoption. We find that changes in the division of labour can result both from reduced production time and from improved communication possibilities. The first shifts the division of labour towards a more generic structure, while the latter enhances specialisation. Although there exists heterogeneity, our estimates for a representative sample of Dutch establishments in the period 1990-1996 suggest that productivity gains have been the main determinant for shifts in the division of labour within most firms. These productivity gains have induced skill upgrading, while in firms gaining mainly from improved communication possibilities specialisation increased and skill requirements have fallen.
Keywords: J31; O15; O33; 330; division of labour; wage level and structure; technological change; computerisation of the labour market